2015
DOI: 10.1038/ncomms6794
|View full text |Cite
|
Sign up to set email alerts
|

ZEB2 drives immature T-cell lymphoblastic leukaemia development via enhanced tumour-initiating potential and IL-7 receptor signalling

Abstract: Early T-cell precursor leukaemia (ETP-ALL) is a high-risk subtype of human leukaemia that is poorly understood at the molecular level. Here we report translocations targeting the zinc finger E-box-binding transcription factor ZEB2 as a recurrent genetic lesion in immature/ETP-ALL. Using a conditional gain-of-function mouse model, we demonstrate that sustained Zeb2 expression initiates T-cell leukaemia. Moreover, Zeb2-driven mouse leukaemia exhibit some features of the human immature/ETP-ALL gene expression sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 50 publications
6
97
0
Order By: Relevance
“…Strikingly, this analysis revealed specific, hormone-dependent deregulation of 2332 (1205 down; 1127 up) and 3205 genes (1456 down; 1749 up) in CAL-1 shGCR and CAL-1 GCR-FP dexamethasone-treated cells, respectively, compared with CAL-1 control cells. Further analysis revealed a common subset of 264 deregulated genes (139 down; 125 up) ( Figure 3B; supplemental Table 13), which included known GCR target genes such as PFKB2 (encoding 6-phosphofructo-2-kinase) and genes encoding nuclear factors that have been implicated in normal (IKZF2/Helios) or leukemic (ZEB2) T lymphoid 39,40 or dendritic cell lineage development (SPIB). 41 Supporting the clinical relevance of the latter findings, deregulated expression of IKZF2, ZEB2, and SPIB was also observed by GEP in primary patient cells with NR3C1 deletion compared with nondeleted control cases (supplemental Figure 3A).…”
Section: Targeting Of Nr3c1 By 5q Anomalies In Bpdcnmentioning
confidence: 99%
“…Strikingly, this analysis revealed specific, hormone-dependent deregulation of 2332 (1205 down; 1127 up) and 3205 genes (1456 down; 1749 up) in CAL-1 shGCR and CAL-1 GCR-FP dexamethasone-treated cells, respectively, compared with CAL-1 control cells. Further analysis revealed a common subset of 264 deregulated genes (139 down; 125 up) ( Figure 3B; supplemental Table 13), which included known GCR target genes such as PFKB2 (encoding 6-phosphofructo-2-kinase) and genes encoding nuclear factors that have been implicated in normal (IKZF2/Helios) or leukemic (ZEB2) T lymphoid 39,40 or dendritic cell lineage development (SPIB). 41 Supporting the clinical relevance of the latter findings, deregulated expression of IKZF2, ZEB2, and SPIB was also observed by GEP in primary patient cells with NR3C1 deletion compared with nondeleted control cases (supplemental Figure 3A).…”
Section: Targeting Of Nr3c1 By 5q Anomalies In Bpdcnmentioning
confidence: 99%
“…It is an oncogenic transcription factor which induces epithelial-mesenchymal transition (EMT) in tumors by binding to and regulating E-cadherin [9]. In a previous study, ZEB2 was found to inhibit squamous transdifferentiation of Lkb1-deficient lung adenocarcinoma by repressing DNp63 through YAP [10] and stimulate immature T-cell lymphoblastic leukemia development via enhanced tumor-initiating potential and IL-7 receptor signaling [11]. In addition, ZEB2 modulated by miR-200b or TMPRSS was associated with EMT and multidrug resistance in lung cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The EMN study did not delineate outcome on the basis of the patients' MYD88 mutation status, nor could the patients be longitudinally evaluated for clonal evolution, a phenomenon that has recently been documented in WM with both PI-based and Bruton tyrosine kinase inhibitor-based therapies. 9 Finally, and most importantly, collaborative efforts remain indispensable in the face of sparse high-level evidence to inform hematologists of the optimal approach to managing WM, a rare and, to date, incurable malignancy. The WM1 study, a phase 3 international trial, demonstrated how consequential the choice of initial therapy can be, even for a typically indolent disorder such as WM; the use of frontline fludarabine favorably affected survival (see table) compared with chlorambucil.…”
mentioning
confidence: 99%
“…Moving forward, additional work needs to be done to more precisely elucidate the molecular mechanisms at play and to investigate the potential development and use of ZEB2 pathway inhibitors as an antileukemic therapy. Such a therapy will likely have a wide range of applicability not only for AML but also in early T-cell precursor acute lymphoblastic leukemia 9 and solid cancers such as breast, 10 colorectal, 11 and liver cancers. 12 However, careful consideration will need to be given to limit the toxicity of this type of differentiation therapy on the remaining normal immune cell populations, which also rely on ZEB2.…”
mentioning
confidence: 99%